Transperitoneal Mini-Laparoscopic Pyeloplasty in Flank Position: A Safe Method for Infants and Young Adults - Bañuelos Marco, Beatriz; Fuller, Tom Florian; Friedersdorff, Frank; González, Ricardo; Lingnau, Anja (Frontiers in Surgery, 2018)
Introduction & Objectives Open dismembered pyeloplasty has been the gold standard treatment for ureteropelvic junction obstruction in children. Laparoscopic pyeloplasty (LP) is becoming a standard procedure, but its acceptance is slow. We report our method for minilaparoscopy (MLP) in children using a tansperitoneal approach with the patient in the lateral flank decubitus which we found technically advantageous. Materials & Methods Retrospective review of the records of 52 children and adolescents up to 18 years of age who underwent transperitoneal MLP at our institution during March 2012-October 2017 A 5 mm trocar is placed for the camera at the site of the umblicus by open technique, two 3 mm trocars placed in the upper and lower quadrants of the abdomen. No additional ports were necessary. 20cm long, 3-mm-diameter instruments are used. Few cases needed percutaneous fixation of the pelvis. The anastomosis is performed with 5-0 or 6-0 Polyglecaprone 25 (Monocryl® ) with 13 mm half circle needle (TF plus) suture cut to 12- 14 cm length and introduced through the 5-mm port. Needles are removed through the 3-mm port under direct vision. Results Fifty-two children (53 renal units) with a mean age of 82 months (range 3,5-204), a mean weight of 24,35 kg (range 7-57), and a mean follow-up of 20,44 months (6-60). Nine children were younger than 12 months, and 14 were ≤10kg. Six patients were >50kg. The mean of preoperative grade of dilatation was III (SFU scale) and postoperatively improved to SFU 0,60 (0-2). In 50 (94,3%) of the cases, there was complete resolution of hydronephrosis. There was no conversions to open surgery. Three patients suffered complications Clavien-Dindo Classification IIIb, 2 omental prolapses through a port site in two children which required general anaesthesia and one percutaneous drainage due to a leakage. No reinterventions related to stent complications or obstruction were found. Mean hospital stay was 4,69 (3-14) days. Conclusions The method of mini LP described here has proven efficient and safe. . Weight appeared not to be limitation for both groups ≤10 kg and >50 kg.